Friedel-Crafts acylation on graphene - Chua, Chun Kiang (2013)
There is an excitement around graphene as a promising new material for nanotechnological and nanoarchitectonic applications. Despite the low chemical reactivity of graphene, chemical functionalization remains a prominent and viable solution to tailor its chemical, physical, and electronic properties. Herein, we report the covalent functionalization of reduced graphene oxide through Friedel–Crafts reactions under mild conditions of polyphosphoric-acid/phosphorus-pentoxide and 4-aminobenzoic acid. Successful functionalization was confirmed by X-ray photoelectron spectroscopy (XPS), FTIR, and Raman spectroscopy. The success of the Friedel–Crafts reaction provides an important expansion of the synthetic “toolbox” for future modifications of graphene towards the specific needs of different applications.